ภาษาจินตภาพในพระราชนิพนธ์เรื่องไกลบ้าน กล้องบันทึกภาพในสารคดีท่องเที่ยวต่างแดนยุคแรกของไทย - วรรณพร พงษ์เพ็ง (2012)
This article is an attempt to study the language of imagery in Klai-ban "Far from Home" of King Rama V to illustrate how the language of imagery is a dominant characteristic that creates imagery, and expresses deep emotions. The elements of the language of imagery are the use of rhyme and rhythm, creative words for describing unfamiliar things, word variation for colour, light, sound, scent, taste, touch, shape and action to identify the uniqueness of things and changing context of word use. In sentence usage, King Chulalongkom uses simple sentences, extra-long modifying sentences and repeating structure of sentences. This usage is intended as a means of ordering and extending imagery. In the use of figure of speech, H.M. King Chulalongkorn uses a large number of simile, metaphor and personification. The value of language of imagery in the texts is two-fold. As an early Thai travelogue, the language of imagery makes Klai-ban a success in conveying the unfamiliar imagery of foreign countries. Moreover, the language of imagery renders a literary beauty to the text.